The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00253-015-6538-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mapping infection-enhancing epitopes of dengue pr protein using polyclonal antibody against prM

Abstract: Dengue vaccine development is considered a global public health priority, but the antibody-dependent enhancement (ADE) issues have critically restricted vaccine development. Recent findings have demonstrated that pre-membrane (prM) protein was involved in dengue virus (DENV) infection enhancement. Although the importance of prM antibodies have been well characterized, only a few epitopes in DENV prM protein have ever been identified. In this study, we screened five potential linear epitopes located at position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
(101 reference statements)
0
19
0
1
Order By: Relevance
“…Recent studies by Luo et al . have analyzed the antibody response to individual epitopes of DENV prM protein. Using epitope mapping and bioinformatic analysis, five epitope peptides were chosen to immunize BALB/c mice from a library of 11 overlapping prM peptides.…”
Section: Characterizing Ade Of Virus Infection: Denv As a Case Studymentioning
confidence: 99%
“…Recent studies by Luo et al . have analyzed the antibody response to individual epitopes of DENV prM protein. Using epitope mapping and bioinformatic analysis, five epitope peptides were chosen to immunize BALB/c mice from a library of 11 overlapping prM peptides.…”
Section: Characterizing Ade Of Virus Infection: Denv As a Case Studymentioning
confidence: 99%
“…Several investigations have reported that anti-prM antibodies have a significant role of enhancing DENV infection (Beltramello et al 2010 ; Dejnirattisai et al 2010 ; Huang et al 2006 ; Rodenhuis-Zybert et al 2010 ). Additionally, it has been demonstrated that the epitopes of these enhancing anti-prM antibodies were mainly located in the amino acid residues of the pr peptide (Dejnirattisai et al 2010 ; Luo et al 2015 ). A previous study also reported that there was relatively low sequence conservation between prM sequences (35 % DENV versus JEV), and only 3 % of the antibodies to dengue prM cross-react with JEV (Dejnirattisai et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that anti-prM monoclonal antibody 4D10, pr4, 2H2, and 70–21 could enhance DENV infectivity. The specific epitopes of 4D10, pr4, 2H2, and 70–21 were mapped to amino acid residues 14–18, 19–34, 40–49, and 53–67 of pr peptide, respectively (Falconar 1999 ; Huang et al 2008 ; Luo et al 2015 , 2013 ). Taken together, these findings indicated the critical role of pr peptide in ADE of DENV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactive epitopes and residues are colored in yellow, type-specific are in red, and residues recognized by both cross-reactive and typespecific monoclonal antibodies are colored in blue. The yellow block represents a region between amino acids 19-34 as an enhancing antibody-binding site (Lin, 2012;Luo, 2013Luo, , 2015Sukupolvi-Petty et al, 2007) presence of the proteins. Cells positive in fluorescence indicate that 4G2 and PrM6.1 recognized their target epitopes on the prM and E complex.…”
Section: Analysis Of Epitopes On (A) Prm and (B) E Genesmentioning
confidence: 99%
“…These binding motifs were also DENV serocomplex cross-reactive. In addition, Luo et al (2015) used a peptide scaning approach to identify a region between amino acids 19-34 of DENV2 prM that can be recognized by anti-DENV from all four serotypes, and showed that these anti-DENV antibodies were infection-enhancing antibodies (Luo et al, 2015).…”
Section: Analysis Of Epitopes On (A) Prm and (B) E Genesmentioning
confidence: 99%